Super-Utilization of the Emergency Department in a Universally Insured Population. Issue 7 (1st July 2021) - Andriotti, Tomas; Dalton, Michael K; Jarman, Molly P; Lipsitz, Stuart; Chaudhary, Muhammad Ali; Tilley, Laura; Learn, Peter A; Schoenfeld, Andrew J; Goralnick, Eric
ABSTRACT: Introduction: Super-utilizers (patients with 4 or more emergency department [ED] visits a year) account for 10% to 26% of all ED visits and are responsible for a growing proportion of healthcare expenditures. Patients recognize the ED as a reliable provider of acute care, as well as a timely resource for diagnosis and treatment. The value of ED care is indisputable in critical and emergent conditions, but in the case of non-urgent conditions, ED utilization may represent an inefficiency in the healthcare system . We sought to identify patient and clinical characteristics associated with ED super-utilization in a universally insured population. Material and Methods: We performed a retrospective cohort study using TRICARE claims data from the Military Health System Data Repository (2011-2015). We reviewed the claims data of all adult patients (aged 18-64 years) who had at least one encounter at the ED for any cause. Multivariable logistic regression was used to determine independent factors associated with ED super-utilization. Results: Factors associated with increased odds of ED super-utilization included Charlson Score ≥2 (adjusted odds ratio [aOR] 1.98, 95% confidence interval [CI]: 1.90-2.06), being eligible for Medicare (aOR 1.95, 95% CI: 1.90-2.01), and female sex (aOR 1.35, 95% CI: 1.33-1.37). Active duty service members (aOR 0.69, 95% CI 0.68-0.72) and beneficiaries with higher sponsor-rank (Officers: aOR 0.50, 95% CI: 0.55-0.57; Senior enlisted: aOR 0.82, 95% CI: 0.81-0.83) had lower odds of ED super-utilization. The most common primary diagnoses for ED visits among super-utilizers were abdominal pain, headache and migraine, chest pain, urinary tract infection, nausea and vomiting, and low back pain. Conclusions: Risk of ED super-utilization appears to increase with age and diminished health status. Patient demographic and clinical characteristics of ED super-utilization identified in this study can be used to formulate healthcare policies addressing gaps in primary care in diagnoses associated with ED super-utilization and develop interventions to address modifiable risk factors of ED utilization.